The pathology of gastric and duodenal polyps: current concepts. Issue 1 (31st December 2020) - Kővári, Bence; Kim, Baek H; Lauwers, Gregory Y
Abstract : The liberal use of upper endoscopy has led to an increased detection of gastric and duodenal polyps, which are identified in as many as 6 and 4.6% of patient examinations, respectively. Gastroduodenal polyps are a heterogeneous group of lesions that can be neoplastic or non‐neoplastic (e.g. hyperplastic or heterotopical). Most polyps present characteristic topographical features, as well as endoscopic appearance and size. Evaluation of the surrounding mucosa is essential in assessing the underlying pathology (e.g. Helicobacter pylori, autoimmune gastritis or inherited polyposis syndromes). Phylogenetically, gastric and duodenal polyps can be classified according to the epithelial compartment from which they derive. Polyps that arise from the surface epithelium can either be of foveolar or intestinal type, and they can develop from either the native mucosa or the metaplastic epithelium (gastric intestinal metaplasia or duodenal foveolar metaplasia). Other polyps develop from the deeper glandular component, such as pyloric/oxyntic gland derived subtypes. In this review we focus upon epithelial polyps, with an emphasis on the most common and clinically relevant lesions, and present recently described entities.